Comparative analysis of the repertoire of G protein-coupled receptors of three species of the fungal genus Trichoderma - Gruber, Sabine; Omann, Markus; Zeilinger, Susanne (BMC microbiology, 2013)
Eukaryotic organisms employ cell surface receptors such as the seven-transmembrane G protein-coupled receptors (GPCRs) as sensors to connect to the environment. GPCRs react to a variety of extracellular cues and are considered to play central roles in the signal transduction in fungi. Several species of the filamentous ascomycete Trichoderma are potent mycoparasites, i.e. can attack and parasitize other fungi, which turns them into successful bio-fungicides for the protection of plants against fungal phytopathogens. The identification and characterization of GPCRs will provide insights into how Trichoderma communicates with its environment and senses the presence of host fungi. We mined the recently published genomes of the two mycoparasitic biocontrol agents Trichoderma atroviride and Trichoderma virens and compared the identified GPCR-like proteins to those of the saprophyte Trichoderma reesei. Phylogenetic analyses resulted in 14 classes and revealed differences not only among the three Trichoderma species but also between Trichoderma and other fungi. The class comprising proteins of the PAQR family was significantly expanded both in Trichoderma compared to other fungi as well as in the two mycoparasites compared to T. reesei. Expression analysis of the PAQR-encoding genes of the three Trichoderma species revealed that all except one were actually transcribed. Furthermore, the class of receptors with a DUF300 domain was expanded in T. atroviride, and T. virens showed an expansion of PTH11-like receptors compared to T. atroviride and T. reesei. Comparative genome analyses of three Trichoderma species revealed a great diversity of putative GPCRs with genus- and species- specific differences. The expansion of certain classes in the mycoparasites T. atroviride and T. virens is likely to reflect the capability of these fungi to establish various ecological niches and interactions with other organisms such as fungi and plants. These GPCRs consequently represent interesting candidates for future research on the mechanisms underlying mycoparasitism and biocontrol.